HERC6 regulates STING activity in a sex-biased manner through modulation of LATS2/VGLL3 Hippo signaling - Ranjitha Uppala; Mrinal K. Sarkar; Kelly Z. Young; Feiyang Ma; Pritika Vemulapalli; Rachael Wasikowski; Olesya Plazyo; William R. Swindell; Emanual Maverakis; Mehrnaz Gharaee-Kermani; Allison C. Billi; Lam C. Tsoi; et al. (iScience, 2024)
Summary: Interferon (IFN) activity exhibits a gender bias in human skin, skewed toward females. We show that HERC6, an IFN-induced E3 ubiquitin ligase, is induced in human keratinocytes through the epidermal type I IFN; IFN-κ. HERC6 knockdown in human keratinocytes results in enhanced induction of interferon-stimulated genes (ISGs) upon treatment with a double-stranded (ds) DNA STING activator cGAMP but not in response to the RNA-sensing TLR3 agonist. Keratinocytes lacking HERC6 exhibit sustained STING-TBK1 signaling following cGAMP stimulation through modulation of LATS2 and TBK1 activity, unmasking more robust ISG responses in female keratinocytes. This enhanced female-biased immune response with loss of HERC6 depends on VGLL3, a regulator of type I IFN signature. These data identify HERC6 as a previously unrecognized negative regulator of ISG expression specific to dsDNA sensing and establish it as a regulator of female-biased immune responses through modulation of STING signaling.